Pengaruh Penggunaan Media Sosial Terhadap Interaksi Sosial Pada Sekaa Teruna Desa Adat Kuta,Badung, Bali - Ratih Mayuni, I Gst. Ayu Agung; Amanda Gelgel, Ni Made Ras; Pascarani, Ni Nyoman Dewi (E-Jurnal Medium, 2017)
The development of social media in Bali is prevalent in the era of cyberspace . This happened in Desa Adat Kuta, especially among Sekaa Teruna (youth organization) of Desa Adat Kuta. Kuta is the center of tourism destinations in Bali with a complete tourist facilities, making it the fastest to experience globalization effects compared to other regions. This study aims to determine the effect of social media use on face to face social interaction in Sekaa Teruna of Desa Adat Kuta. This research uses quantitative research method in explanative form and inferential statistic data analysis. The quantitative data was collected by survey method, using questionnaire as main instrument of research. Stratified random sampling was used as sampling technique. The data analysis technique used is a simple linear regression test with data processing using SPSS program computational calculation. The results showed that the use of social media significantly have positive effect on face to face social interaction in Sekaa Teruna Desa Adat Kuta, Badung, Bali. These results indicate that the higher the use of social media then the higher the face to face social interaction on Sekaa Teruna Indigenous Villages Kuta, Badung, Bali.